Effects of different feeding strategies for the frozen Antarctic krill meal on growth, muscle nutrition, digestive enzyme activity, immunity, molting, and gut microbiota structure of Cherax quadricarinatus - Mai, Zhuang; Wei, Jie; Wang, Yakun; Zeng, Zhongqiang; Liu, Fubai; Li, Huarong; Su, Qiyao; Hong, Kunhao; Zhou, Qiaoyan; Jiao, Tianhui; Yang, Tianyan; Yu, Lingyun (Frontiers in Marine Science, 2025)
To investigate the effect of the frozen Antarctic krill meal (AKM) as an nutritional supplement in Cherax quadracarinatus culturing, an experiment was designed with the following groups: a control group (C) fed with basic feed throughout the experiment; Experimental Group 1 (E1) fed basic feed for 2 d and then compound feed (50% AKM + 50% basic feed) for 1 d; Experimental Group 2 (E2) fed basic feed for 1 d and then compound feed (50% AKM + 50% basic feed) for 1 d; Experimental Group 3 (E3) fed compound feed (50% AKM + 50% basic feed) daily. After 10 weeks of feeding, growth results revealed that both E1 and E2 groups exhibited significantly higher weight gain rate (WGR) and specific growth rate (SGR) compared to groups C and E3 (p < 0.05), with E2 achieving the highest survival rate (SR). Regarding muscle nutrition, the contents of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in C. quadracarinatus muscle showed a gradual increase with higher AKM feeding levels (p < 0.05), while the highest astaxanthin content was observed in group E2. Analysis of digestive enzyme activity and fluorescence quantification demonstrated that feeding AKM every other day (E2) not only enhanced the activities of trypsin and lipase in the hepatopancreas but also upregulated the expression levels of immune-related and molting-related genes (p < 0.05), whereas daily AKM feeding showed no significant improvements. Additionally, AKM feeding influenced the intestinal microbiota structure and abundance, with a notable increase in Bacteroidota phylum abundance in group E2.In conclusion, this study demonstrates that alternate-day AKM feeding (E2) optimizes growth performance, enhances muscle nutritional quality, improves digestive and immune capacities, and modifies intestinal microbiota composition in red claw crayfish. In contrast, daily AKM feeding, while elevating certain nutritional indices (e.g., EPA+DHA), exhibits limited benefits for overall growth performance and physiological function enhancement. Therefore, alternate-day AKM feeding is recommended as a superior strategy, providing scientific evidence for its application in C. quadracarinatus aquaculture.